DEVELOPING RESIN MEDIA IN MAGNOLIOPSID CLASS OF CHRYSANTHEMUM PLANTS AS A BIOLOGY LEARNING MEDIA - Rahmadina Rahmadina; Efrida Pima Sari Tambunan (UIN Sumatera Utara Medan, 2019)
The purpose of this study was to determine the process of developing block resin media in the Magnoliopsida class Chrysanthemum plant and also the level of feasibility of the resin media as a biology learning media using development methods based on Borg & Gall combined with Dick & Carey learning in 5 stages, namely: (1) Stage of needs analysis, formulating instructional objectives, product validation, product trials, and revisions. Analysis of data in the form of a Likert scale to determine the feasibility of the media analyzed by qualitative descriptive. The results showed that the block resin media ware suitable to be used as a learning medium based on the results of validation tests from material experts (79.1%), media experts (84.1%) and trials on lecturers and Peer Reviewers (84.05%), and product trials in individual trials (81.6%), small group trials (83%), limited field group trials (79.5%). Through this media, it is hoped that it can improve the effectiveness and motivation of students in the Biology departmentat the Faculty of Science and Technology of the State Islamic University of North Sumatra.